PENAMBAHAN KOLAGEN SISIK DAN TULANG IKAN GURAMI (Osphronemus goramy) PADA MINUMAN JUS JAMBU BIJI (Psidium guajava L) - Widjaja, Willy Pranata (Department of Food Technology, Universitas Pasundan, Bandung, 2019)
The addition of collagen derived from bone and scales gouramy into red guava juice drinks and the characteristics of collagen red guava juice drinks based on chemical, physical and organoleptic properties was done. This study used a 5x5 factorial experimental design in a factorial randomized block design (RCBD) with 5 replications, which included factors: added collagen concentration, namely a1 (1%), a2 (1.5%), a3 (2%), a4 (2.5%), a5 (3%). The analysis responses included organoleptic responses (taste, aroma and color), physical responses (viscosity) and chemical responses (protein content and Vitamin C levels). The results of this study indicate that the concentration of collagen added to red guava juice drinks affect the response of taste, aroma, viscosity, protein and Vitamin C from red guava juice drinks. The concentration of collagen added to the red guava juice drink has no effect on the color of the drink